Tracking and characterization of a novel conjugative transposon identified by shotgun transposon mutagenesis - Ortañez, Jericho; Degnan, Patrick H. (Frontiers in Microbiology, 2024)
The horizontal transfer of mobile genetic elements (MGEs) is an essential process determining the functional and genomic diversity of bacterial populations. MGEs facilitate the exchange of fitness determinant genes like antibiotic resistance and virulence factors. Various computational methods exist to identify potential MGEs, but confirming their ability to transfer requires additional experimental approaches. Here, we apply a transposon (Tn) mutagenesis technique for confirming mobilization without the need for targeted mutations. Using this method, we identified two MGEs, including a previously known conjugative transposon (CTn) called BoCTn found in Bacteroides ovatus and a novel CTn, PvCTn, identified in Phocaeicola vulgatus. In addition, Tn mutagenesis and subsequent genetic deletion enabled our characterization of a helix-turn-helix motif gene, BVU3433 which negatively regulates the conjugation efficiency of PvCTn in vitro. Furthermore, our transcriptomics data revealed that BVU3433 plays a crucial role in the repression of PvCTn genes, including genes involved in forming complete conjugation machinery [Type IV Secretion System (T4SS)]. Finally, analysis of individual strain genomes and community metagenomes identified the widespread prevalence of PvCTn-like elements with putative BVU3433 homologs among human gut-associated bacteria. In summary, this Tn mutagenesis mobilization method (TMMM) enables observation of transfer events in vitro and can ultimately be applied in vivo to identify a broader diversity of functional MGEs that may underly the transfer of important fitness determinants.